Design of Functional Powdered Beverages Containing Co-Microcapsules of Sacha Inchi P. huayllabambana Oil and Antioxidant Extracts of Camu Camu and Mango Skins - Chasquibol, Nancy (2022)
Sacha inchi Plukenetia huayllabambana oil (SIPHO) was co-microencapsulated, by spray drying using gum arabic as a coating material, with antioxidant extracts of camu camu (Myrciaria dubia (HBK) McVaugh) (CCSE) and mango (Mangifera indica) (MSE) skins obtained by ultrasound–microwave-assisted extraction (UMAE). The physicochemical characteristics of the microcapsules, such as, particle size, morphology, and moisture, as well as the encapsulation efficiency, the fatty acid composition, and oxidative stability, were determined in order to select the best formulation for the design of functional powdered beverages. The formulation with the highest amounts of ω3 acids and polyphenols was used to prepare a functional powdered beverage that contained ω3 (52.74%), antioxidant activity (324.80 mg AAE/100 g powder), and acceptable sensory attributes. Resumen: Se co-microencapsuló aceite de sacha inchi Plukenetia huayllabambana (SIPHO), mediante secado por aspersión utilizando goma arábiga como material de recubrimiento, con extractos antioxidantes de camu camu (Myrciaria dubia (HBK) McVaugh) (CCSE) y mango (Mangifera indica) (MSE) pieles obtenidas por extracción asistida por ultrasonido-microondas (UMAE). Se determinaron las características fisicoquímicas de las microcápsulas, tales como tamaño de partícula, morfología y humedad, así como la eficiencia de encapsulación, la composición de ácidos grasos y la estabilidad oxidativa, con el fin de seleccionar la mejor formulación para el diseño de bebidas funcionales en polvo. . La formulación con las mayores cantidades de ácidos ω3 y polifenoles se utilizó para preparar una bebida en polvo funcional que contenía ω3 (52,74 %), actividad antioxidante (324,80 mg AAE/100 g de polvo) y atributos sensoriales aceptables.